2019
DOI: 10.1101/516468
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Visualizing structural transitions of ligand-dependent gating of the TRPM2 channel

Abstract: The calcium-permeable transient receptor potential melastatin 2 (TRPM2) channel plays a key role in redox sensation in many cell types 1-3 . Channel activation requires binding of both ADP-ribose (ADPR) 2,4-6 and Ca 2+ 7 . The recently published TRPM2 structures from Danio rerio in the ligand-free and in the ADPR/Ca 2+ -bound conditions represent the channel in closed and open states, which uncover substantial tertiary and quaternary conformational rearrangements 8 .However, it is unclear how these rearrangeme… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 52 publications
2
2
0
Order By: Relevance
“…Hence, the channel might be utilizing C2 symmetric states as means to achieve full opening in a step-wise manner. Similar C2 symmetric states elicited by ligand binding have been observed in TRPV3 33 and TRPM2 37 channels, which opens up the possibility that C2 symmetry might be widely associated with gating in members of the TRP channel superfamily. Intriguingly, a recent cryo-EM study of the human BK channel reconstituted in liposomes showed that this channel also enters C2 symmetric states 38 , suggesting that two-fold symmetry might also play a role in the molecular mechanisms of other tetrameric ion channels.…”
Section: Discussionsupporting
confidence: 65%
“…Hence, the channel might be utilizing C2 symmetric states as means to achieve full opening in a step-wise manner. Similar C2 symmetric states elicited by ligand binding have been observed in TRPV3 33 and TRPM2 37 channels, which opens up the possibility that C2 symmetry might be widely associated with gating in members of the TRP channel superfamily. Intriguingly, a recent cryo-EM study of the human BK channel reconstituted in liposomes showed that this channel also enters C2 symmetric states 38 , suggesting that two-fold symmetry might also play a role in the molecular mechanisms of other tetrameric ion channels.…”
Section: Discussionsupporting
confidence: 65%
“…Hence, the channel might be utilizing C2 symmetric states as means to achieve full opening in a step-wise manner. Similar C2 symmetric states elicited by ligand binding have been observed in TRPV3 (Zubcevic et al, 2018b) and TRPM2 (Yin et al, 2018) channels, which opens up the possibility that C2 symmetry might be widely associated with gating in members of the TRP channel superfamily. Intriguingly, a recent cryo-EM study of the human BK channel reconstituted in liposomes showed that this channel also enters C2 symmetric states (Tonggu and Wang, 2018), suggesting that two-fold symmetry might also play a role in the molecular mechanisms of other tetrameric ion channels.…”
Section: Discussionsupporting
confidence: 61%
“…We favor the former, because the structure of ADPR/Ca 2+ - hs TRPM2 is nearly identical with the non-activated ADPR- hs TRPM2. Moreover, the recently published two-fold symmetric dr TRPM2 adopts a hybrid of alternating non-flipped and flipped conformation of the S4-S5 linkers in TMD (Yin et al, 2019b), the former of which represents an intermediate state after ligand binding but prior to channel opening, which is similar to the TMD conformation of in our ADPR/Ca 2+ -bound hs TRPM2 structure. This further supports that the ADPR/Ca 2+ -bound hs TRPM2 structure represents a pre-open state.…”
Section: Resultsmentioning
confidence: 52%
“…The hs TRPM2 structures share a four-layer arrangement with dr TRPM2 (Huang et al, 2018; Yin et al, 2019b), having a TMD, MHR3/4, and a ligand-sensing layer that includes the MHR1/2 and NUDT9-H domains, from top to bottom. However, their overall shapes differ, primarily because the NUDT9-H domain is positioned differently.…”
Section: Resultsmentioning
confidence: 99%